The Effect of Eco enzyme Application method on the Growth of Land Kangkung (Ipomea reptans Poir.) - Ilham Rizky Ritonga; Azwir Anhar (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Kangkung is one type of vegetable that is much favored by the people of Indonesia, Kangkung has high nutritional value, especially vitamin A, vitamin C, iron, calcium, and phosphorus. The type of organic fermentation that has the potential and is not widely known to the public is ecoenzyme liquid organic fertilizer. The level of effectiveness of nutrient absorption depends on several factors, one of which is the method of applying fertilizer. The purpose of this study was to determine the effect of the administration of ecoenzymes on the growth of land kangkung (Ipomea reptans Poir.). This study is an experimental study using a Completely Randomized Design (CRD) consisting of 4 treatments and 6 replications. The treatments given were soaked seeds, soaked roots, watered to the ground, sprayed leaves. The data obtained were analyzed by means of variance (ANOVA). The results showed that the method of administration with soaked seeds (P1) gave the best results at the age of 2,3,4, and 5 weeks after planting (MST) based on height, leaf area, wet weight and dry weight of the plant. In this study, it was found that the method of administering ecoenzymes had no effect on the growth of land kangkong.